General Account of Flora - Meekiong, Kalu; Mohd Effendi, Wasli (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
Niah National Park, located in Sarawak, Malaysia, is a remarkable site for its archaeological history and diverse ecosystems. Covering approximately 3,140 hectares, the Park is renowned for its limestone hills, rainforests and an intricate network of caves. The climate is tropical, with high humidity and rainfall throughout the year, creating an ideal environment for its flora. Further, the Park’s elevational diversity and geology contribute to the distinct vegetation zones present within its boundaries.